2017
DOI: 10.15835/buasvmcn-fst:11591
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiles and Antioxidant Activity of Black Elder (Sambucus Nigra L.) - A Review

Abstract: All plant parts of black elder (leaves, berries, inflorescences, roots, shoots, bark) have a long history of use in herbal remedy or lots of culinary uses, widespread in almost every continent of the world. Pro-health properties indicated a role of black elderberry products intake in the prevention of cancer and diabetes. This paper presents an overview of the evaluation of biochemical compounds (sugars, organic acids, total phenolics, antioxidative activity, flavonoids, flavor and volatile compounds), found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In addition, freeze-dried elderberry, as compared to chokeberry, had a higher content of flavonoids (Table 3). Several studies have confirmed that elderberry is a valuable raw material with many nutrients and bioactive substances (Petrut et al, 2017). Elderberry displays a high concentration of compounds with antioxidative activity, especially anthocyanins, flavonoids and vitamins (Matejicek et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, freeze-dried elderberry, as compared to chokeberry, had a higher content of flavonoids (Table 3). Several studies have confirmed that elderberry is a valuable raw material with many nutrients and bioactive substances (Petrut et al, 2017). Elderberry displays a high concentration of compounds with antioxidative activity, especially anthocyanins, flavonoids and vitamins (Matejicek et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…1 Moreover, elderberry flowers, fruits, and leaves also contain various bioactive compounds, including phenolics, flavonoids, and volatile compounds, especially rich in antioxidant phytochemicals. 2 Elderberry has been traditionally used as an herbal medicine with different functions. Its flowers have been approved by the United States Food and Drug Administration to be used as flavoring ingredients, and they are generally recognized as safe.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Also, the use of Sambucus nigra by the Sete Cidades community as an antidiarrheal and antipyretic (Table 1) does not seem to be supported by scientific studies. In fact, despite the broad biological activities of Sambucus nigra [55,56,57,58], the consumption of the immature plant or high quantities of fruits may cause diarrhoea itself, as well as nausea and vomiting [59].…”
Section: Discussionmentioning
confidence: 99%